Redescription of Tanaisia dubia (Digenea) from the northeast region of Argentina, with a key to Neotropical species of the genus, and a key to genera of Tanaisiinae - Lunaschi de Redolatti, Lía Inés (2015)
Tanaisia dubia Freitas, 1951 (Digenea: Eucotylidae) is redescribed on the basis of specimens collected from the urinary tubules of the White-backed Stilt Himantopus melanurus (Charadriiformes: Recurvirostridae), and the Great Kiskadee Pitangus sulphuratus (Passeriformes: Tyrannidae), from Argentina. The specimens studied here are consistent with the original description, which was based on 1 specimen found parasitizing the Gray Yellowlegs Tringa melanoleuca (Charadriiformes, Scolopacidae), from Brazil. This redescription adds new morphological characters and enlarges the range of morphometric data for this species. A key to the genera of Tanaisiinae, as well as one for Neotropical species of Tanaisia Skrjabin, 1924 are presented. The diagnosis of Tanaisiinae is emended to include the presence of a cirrus sac. T. dubia is reported for the first time in Argentina and H. melanurus and P. sulphuratus represent new host records.